Because in parenthesis you have to multiply it by something.
if you take your time youll figure out its e=mc2
x cubed y cubed z squared
you distribute the negative to the inside of the parenthesis
(x2y2)3 + (x3y3)2 = 2x6y6.
It's hard to be sure that I definitely understand the question. Let's see if this helps: (122) = 144, so -(122) = -144 (-122) = 144, so -(-122) = -144
(-5)-2 = 1/(-5)2 = 1/25 = 0.04
negative 2 squared
it equals positive one. one squared is always one. if they're both negative, negative times negative is always positive.
75r^2-48 You can take out 3.So... 3(25r^2-16) 3-parenthesis-25r squared-minus-16-parenthesis (: